The association between resting heart rate, cardiovascular disease and mortality: evidence from 112, 680 men and women in 12 cohorts. (June 2014) - Woodward, Mark; Webster, Ruth; Murakami, Yoshitaka; Barzi, Federica; Lam, Tai-Hing; Fang, Xianghua; Suh, Il; Batty, G David; Huxley, Rachel; Rodgers, Anthony
Background: Multiple studies have examined the relationship between heart rate and mortality; however, there are discrepancies in results. Our aim was to describe the relationship between resting heart rate (RHR) and both major cardiovascular (CV) outcomes, as well as all-cause mortality in the Asia-Pacific region. Design and methods: Individual data from 112, 680 subjects in 12 cohort studies were pooled and analysed using Cox models, stratified by study and sex, and adjusted for age and systolic blood pressure. Results: During a mean 7.4 years follow-up, 6086 deaths and 2726 fatal or nonfatal CV events were recorded. There was a continuous, increasing association between having a RHR above approximately 65 beats/min and the risk of both CV and all-cause mortality, yet there was no evidence of associations below this threshold. The hazard ratio (95% CI) comparing the extreme quarters of RHR (80+ v <65 beats/min) was 1.44 (1.29–1.60) for CV and 1.54 (1.43–1.66) for total mortality. These associations were not materially changed by adjustment for other risk factors and exclusion of the first 2 years of follow-up. Hazard ratios of a similar magnitude were found for ischemic and hemorrhagic stroke, but the hazard ratio for heart failure was higher (2.08, 95% CI 1.07–4.06) and for Coronary Heart Disease (CHD) was lower (1.11, 95% CI 0.93–1.31) than for stroke. Conclusions: RHR of above 65 beats/min has a strong independent effect on premature mortality and stroke, but a lesser effect on CHD. Lifestyle and pharmaceutical regimens to reduce RHR may be beneficial for people with moderate to high levels of RHR.